Extracellular vesicles mediated exocytosis of antisense peptide nucleic acids - Shipra Malik; W. Mark Saltzman; Raman Bahal (Elsevier, 2021)
Peptide nucleic acids (PNAs), a synthetic DNA mimic, have been extensively utilized for antisense- and antigene-based biomedical applications. Significant efforts have been made to increase the cellular uptake of PNAs, but here we examined relatively unexplored aspects of intracellular trafficking and endocytic recycling of PNAs. For proof-of-concept, we used anti-microRNA (miR) PNA targeting miR-155. The sub-cellular localization of PNA was studied via confocal and flow-cytometry-based assays in HeLa cells. A comprehensive characterization of PNA-containing extracellular vesicles revealed spherical morphology, negative surface charge density, and the presence of tetraspanin markers. Most importantly, we investigated rab11a and rab27b GTPases' role in regulating the exocytosis of PNAs. Organelle staining, followed by confocal imaging, showed higher localization of PNA in lysosomes. Gene-expression analysis established the enhanced functional activity of PNA after inhibition of endocytic recycling. Multiple studies report the exocytosis of single-stranded oligonucleotides, short interfering RNAs (siRNAs), and nanocarriers. To our knowledge, this is the first mechanistic study to establish that PNA undergoes endocytic recycling and exocytosis out of tumor cells. The results presented here can serve as a platform to develop and optimize strategies for improving the therapeutic efficacy of PNAs by avoiding the recycling pathways.